Contemporary Maqasid Renewal: Models and Methods - ’Atyia يوسف (Journal of Contemporary Maqasid Studies, 2024)
The investigation of the Book of Al Mouwafakat (The reconciliations) by Imam Al-Shatibi constituted a resumption of the process of ijtihad and renewal in the fundamental lesson of objectives and a new awakening of the Muslim mind in general. The Maqasid lesson therefore experienced a new phase in terms of composition, classification, and interest, and then the prime objectives of the Shari’ah got a consensus among students, thinkers, and diligent scholars alike. It has also become the most requested thing among all trends of contemporary Islamic thought, regardless of the multiplicity and difference of their intellectual premises and references. Purposeful practice and purposeful thought have become a basic requirement, not only from within the Shari’ah sciences, but also from other cognitive circles, including social, political, economic, and experimental ones. However, this increasing interest in the field of objectives was not free from problems and imbalances, some of which were linked to the approach that deals with them, while others were linked to the method of employing them. Such a situation made some people fear the field of objectives, just as those before them had feared the call to open the door to ijtihad, which contributed to the emergence of two groups that stood on opposite sides in dealing with the purposes of Shari’ah law and in implementing it (one group was fearful and the other was lax), or to say it otherwise (one was rebellious and the other was hesitant). So, it was necessary for a third party to emerge so as to redress the balance, a moderate and just party that constantly seeks to control the course of the objectives and clarify the intention of each intended ,for the sake of protecting its scope and securing its fruits. This is so that the lesson of objectives is freed from those who are fearful as well as from those who are negligent. Hence, a group of virtuous people rose to that task, carrying diligent and innovative visions. They mainly sought to renew the Maqasid and fundamentalist lesson in general. So, to what extent did their renewal efforts succeed in what they called for and worked on? Were their efforts sufficient to answer the question of renewal in the fundamental lesson of objectives? And what are the foundations and mechanisms on which they built their innovative projects?